Aplikasi Penambahan Cacing Tanah (Lumbricus rubellus) pada Pakan Induk Lele Sangkuriang (Clarias sp.) [Applications of Addition Earthworms (Lumbricus rubellus) on Feed of Sangkuriang Catfish (Clarias sp.) ] - Abdul Manan; Anggit Puspitasari (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Aquaculture production from 2010 to 2014 has increased. The average increase catfish production reached 35%. Increased production resulted in increased seed requirement can be met if the fish seed production is done in bulk and sustainable. The use of artificial feeding has an important role to support aquaculture activities. Sangkuriang catfish broodstock must obtain amino acids from protein feed for the growth of reproductive glands, development and construction of new tissue and repair damaged tissue. Earthworm protein quality higher than meat and fish proteins make earthworms likely used as fish feed ingredients. Purpose of this study is to know aplication of the addition earthworm (Lumbricus rubellus) at the sangkuriang catfish (Clarias sp.) broodstock feed. Study was conducted in BBPBAT Sukabumi, West Java on January 20 to February 14, 2014. Working methods used is a descriptive method. Data were collected by means of observation, participation and interviews. The process of making the sangkuriang catfish broodstock feed with the addition of earthworms consists of several stages of harvesting earthworms, weighing, mixing some of the material feed, milling, mixing the remaining feed ingredients, printing, and storage. Proximate analysis showed higher levels of crude protein (PK) of the parent sangkuriang catfish feed by 28%.